Analysis of the potential geographical indication for ovine and caprine from the semiarid piauiense (Research, Society and Development, 2023)
geographical indication is an intangible asset of industrial property that aims to distinguish the geographical origin of a given product or service, functioning as a collective instrument for the distinction, protection and enhancement of traditional products from a given region. This research aims to analyze the potential for certification by geographical indication for ovine and caprine meat produced in the semi-arid region of Piauí. Data collection was carried out from searches in the Google and Google Scholar databases, using two search protocols to verify the academic and informational notoriety of the production of ovine and caprine meat in the semi-arid region of Piauí. The data were analyzed considering the requirements and conditions for granting the Geographical Indication registration, defined by the National Institute of Industrial Property. More than 9,000 results for academic publications and 195,500 results for informational literature were identified from the search protocols, related to the productive chain of ovine and caprine in the semi-arid region of Piauí. The results showed that the semi-arid region of Piauí is recognized as a center for the production of ovine and caprines meat, one of the requirements for granting a Geographical Indication in the form of an Indication of Origin, in accordance with the concession legislation. As for the Designation of Origin, considering the requirements for granting the seal by the certifier, it is necessary to broaden the scope of the study in order to identify the qualities or characteristics of ovine and caprine meat that are due exclusively or essentially to the peculiarities of the geographical environment, including natural and human factors.